Praca a wartości w badaniach nauk społecznych - Żechowski, Zbigniew Antoni (Wydział Prawa i Administracji UAM, 1988)
The article contains reflections on wide or narrow understanding of work in the theory and research praxis of sociology, psychology and pedagogics. It shows wide understanding of work in philosophical axiology and anthropology and then it presents a partition of that object of research done by social sciences. The article focuses its attention on research on work for remuneration, especially on work in industry, i.e. the most advanced research on work in Poland and contains a review of various research trends: „social engineering" together with humanistic and personalistic approaches. The author links with the latter approaches the research on human activity set in the perspective of values. The author takes a critical attitude both with respect to „social engineering" trends in sociology and psychology of industry as well as towards some more recent „medium range" theories (a theory of needs, of orientation, of motivation, a theory of regulation of behaviours, of values). The author finds in those theories a common „manipulatory" orientation which performs adaptative and preservative functions with respect to the social system. The author confronts them with, the postulated critical-reformatory orientation which, taking as a starting point a wholistic understanding of socio-historical praxis, were to be useful in implementing a deep reform of the society in a transition period from capitalism to socialism.
Work and values in social sciences research